Single-cell RNA-seq analyses inform necroptosis-associated myeloid lineages influence the immune landscape of pancreas cancer - Dong, Weiwei; Zhao, Huixia; Xiao, Shanshan; Zheng, Liuqing; Fan, Tongqiang; Wang, Li; Zhang, He; Hu, Yanyan; Yang, Jingwen; Wang, Tao; Xiao, Wenhua (Frontiers in Immunology, 2023)
Tumor-infiltrating myeloid cells (TIMs) are key regulators in tumor progression, but the similarity and distinction of their fundamental properties in pancreatic ductal adenocarcinoma (PDAC) remain elusive.In this study, we conducted scRNA-seq data analysis of cells from primary, metastatic, paratumor, and PBMC samples across 16 PDAC patients, and revealed a heterogeneous TIMs environment in PDAC.Systematic comparisons between tumor and non-tumor samples of myeloid lineages identified 10 necroptosis-associated genes to be upregulated in PDAC tumors compared with 5 being upregulated in paratumor or healthy peripheral blood. A novel RTM (resident tissue macrophages), GLUL -SQSTM1 - RTM, was found to act as a positive regulator of immunity. Meanwhile, HSP90AA1 + HSP90AB1 + mast cells were found to be pro-immune, while HSP90AA1-HSP90AB1-mast cells were pro-tumor. Furthermore, JAK3 + TLR4 + CD16 monocytes were found to be anti-immune, while JAK3 -TLR4 -CD16 monocytes were pro-immune. Clinical outcomes and cytokines analyses validated the findings. Finally, intercellular network reconstruction supported the associations between the identified novel clusters, cancer cells, and immune cell populations. Our collective view of the cellular myeloid landscape and intercellular interactions in PDAC provides valuable mechanistic insights for the design of effective immuno-oncology treatment strategies.